2020
DOI: 10.1530/ec-20-0035
|View full text |Cite
|
Sign up to set email alerts
|

SST5 expression and USP8 mutation in functioning and silent corticotroph pituitary tumors

Abstract: Objective Somatostatin receptor type 5 (SST5) is inconsistently expressed by corticotroph tumors, with higher expression found in corticotropinomas having ubiquitin-specific protease 8 (USP8) mutations. Aims were to study the correlation between characteristics of corticotropinomas and SST5 expression/USP8 mutation status and to describe the response to pasireotide in five patients. Design Retrospective cohort study. Methods Clinico-biochemical, radiological and pathological data of 62 patients, operated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…These results raise the question of whether this may also be the case for other SSTs and whether the histological subtype may be a predictor of response to SSTs ligands. Moreover, from a biological point of view, it suggests that different tumorigenesis mechanisms may be responsible for SST2+ versus SST2− gonadotroph tumors, as recently proposed for SST5+ versus SST5− corticotroph PitNETs [20,21].…”
Section: Discussionmentioning
confidence: 59%
“…These results raise the question of whether this may also be the case for other SSTs and whether the histological subtype may be a predictor of response to SSTs ligands. Moreover, from a biological point of view, it suggests that different tumorigenesis mechanisms may be responsible for SST2+ versus SST2− gonadotroph tumors, as recently proposed for SST5+ versus SST5− corticotroph PitNETs [20,21].…”
Section: Discussionmentioning
confidence: 59%
“…The mutations are less frequent in this group of patients than in the case of Cushing's disease. We identified the mutations in 20% of patients, while the mutation rate was 10% in the other study by Castellnoum, which included 20 SCAs [9]. No SCA with mutation was found in a study that included 11 such patients [6].…”
Section: Discussionmentioning
confidence: 66%
“…Recently, notable progress in the understanding of pathogenesis of CD has been made [3], including the discovery of recurrent USP8 mutations [4][5][6]. These mutations are observed in approximately 30-40% of patients suffering from Cushing's disease as well as in silent tumors [4,[6][7][8][9]. Patients with Cushing's disease with and without USP8 mutations have a slightly different clinical profile according to previously published data [4,6,8,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 84%
“…The frequency of USP8 mutations observed in our cohort is lower than in most cohorts described so far. Indeed, according to a recent published meta-analysis, USP8 somatic mutations have been reported in about 35% (20-60%) of cases [10], with the lowest and highest prevalence registered in European studies [16,22,34] and a large Chinese cohort [3], respectively, probably suggesting a role of genetic background and ethnicity differences. Mutations in USP48 and BRAF have also been recently detected in corticotroph tumors, mostly wild type for USP8 itself [9,24,35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that V600E variant has an increased kinase activity, resulting in activation of MAPK pathway and elevation of POMC transcription and ACTH synthesis [9]. Following the identification of driver mutations in ACTH-secreting tumors, in the past few years many groups reported the results of genetic analysis of CD patients, mainly performed for USP8 by exome sequencing or targeted sequencing [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The aim of the present study was to characterize the genetic profile of a cohort of 60 patients subjected to surgery excision of ACTH-secreting tumors, searching for somatic mutations in USP8, USP48, and BRAF hotspot regions.…”
Section: Introductionmentioning
confidence: 99%